Fiscal Sustainability in Burundi : Baseline Projections, Stochastic Simulations, and Policy Scenarios - Kida, Mizuho (World Bank, Washington, DC, 2013)
This paper analyzes Burundi's medium-term fiscal sustainability in the light of the country's vulnerability to various shocks. Earlier studies have highlighted the country's vulnerability to exogenous shocks related to commodity exports, rain-fed agriculture, and volatile foreign aid. Internally, uncertainty about the implementation of the government's fiscal reforms is a key risk. The earlier studies, however, did not quantify the size and impact of the risks on the country's fiscal sustainability. Drawing initially on the standard inter-temporal sustainability framework, the baseline analysis shows that Burundi's ongoing fiscal policy strategy is not sustainable, even with a gradually improving external environment and relatively strong growth. Stochastic simulations show that adverse shocks to rainfall or coffee prices could increase the country's debt-to-gross domestic product ratio by 5 to 7 percentage points above the projected baseline ratio. Aid shocks could have an even larger impact but the estimates are less statistically reliable because of the short time series and because historical volatility in part reflects endogenous shocks (such as reform implementation) as well as exogenous shocks (donors' behavior). The policy scenario analysis shows that future fiscal sustainability will hinge on the government's ability to stick to its plans to broaden the tax base, streamline generous tax incentives and exemptions, and control civil service wages and short-run expenditure pressures -- risks that need to be monitored closely over the political cycle in the country.